Communication Rx : transforming healthcare through relationship-centered communication - Chou, Calvin L.; Cooley, Laura (Laura A.) (McGraw-Hill Education, 2018)
An invaluable step-by-step guide, this practical book provides institutional initiatives to help you implement change in your organization and outlines a field-tested blueprint for healthier communication across the entire industry. --